A Study on the Improvement of the Evaluation Scale of Discomfort Glare in Educational Facilities - Sewon Lee; Kyung Sun Lee (Energies, 2019)
The lighting environment is a factor that significantly affects the physical and psychological aspects of occupants of a building. In particular, educational facilities should be designed to provide adequate natural lighting because it has a profound impact on students’ health and learning performance. Although environmental certification systems include evaluation items for improving the indoor light environment, there is a lack of evaluation criteria regarding the corresponding issue of glare. Therefore, this study aims to help visualize areas where indoor glare problems occur, and to improve the evaluation scale of discomfort glare in environmental certification systems. A standard high school classroom in Seoul was analyzed to study glare issues in the educational space. DIVA for Rhino—Grasshopper, a light environment simulation program based on Radiance and DAYSIM program, was used to obtain reliable light analysis simulation results, and the daylight glare probability (DGP) measure was used to calculate discomfort glare. The results of the simulation and analysis suggest this is a method for improving glare evaluation measures that are lacking in indoor environmental certification standards. The visualized frequency of discomfort glare data is useful for planning the layout of the indoor space, opening, and shading design of a building to prevent glare problems.